Preparation and In Vitro Drug Release Behavior of 1,10-Phenanthroline/β-cyclodextrin–poly (Glycidyl Methacrylate) Drug-Loaded Microspheres - Li, Ya; Zhen, Weijun (Journal of Research Updates in Polymer Science, 2017)
In this study, novel star-shaped polymers of β-cyclodextrin (β-CD)–poly (glycidyl methacrylate) (PGMA) were prepared by atom transfer radical polymerization (ATRP), formed from GMA and β-CD. In addition, the structure, properties and hydrophilicity of the β-CD-PGMA polymers thus prepared were systematically analyzed. 1,10-phenanthroline monohydrate (Phen)/β-CD-PGMA drug-loaded microspheres were prepared by emulsion solvent evaporation. The optimum preparation conditions were determined by orthogonal tests. Analysis results indicated that the performance of star-shaped polymers of β-CD-PGMA clearly changes, resulting in the increase of the contact angle from 17° to 72.5°, and their thermal degradation temperature was enhanced from 260 °C to 401 °C. Moreover, β-CD-PGMA drug-loaded microspheres with a smooth, spherical surface were successfully prepared, and the drug-loading capacity and average particle size of drug-loaded microspheres were 26.67 % and 10 μm, respectively. Drug release tests indicated that the release behavior of β-CD-PGMA drug-loaded microspheres conformed to Higuchi release kinetics, which exhibited a significant drug delivery capability. The release rate and utilization of β-CD-PGMA were greater than that of β-CD, demonstrating that β-CD-PGMA was more suitable as a drug delivery material.